Integrative analysis of mRNA and microRNA expression of a human alveolar epithelial cell(A549) exposed to water and organic‐soluble extract from particulate matter (PM)2.5. Issue 1 (20th January 2016) - Jeong, Seung‐Chan; Song, Mi‐Kyung; Cho, Yoon; Lee, Eunil; Ryu, Jae‐Chun
ABSTRACT: MicroRNA (miRNA) is now attracting attention as a powerful negative regulator of messenger RNA(mRNA) levels, and is implicated in the modulation of important mRNA networks involved in toxicity. In this study, we assessed the effects of particulate matter 2.5 (PM2.5 ), one of the most significant air pollutants, on miRNA and target gene expression. We exposed human alveolar epithelial cell (A549) to two types of PM2.5 [water (W‐PM2.5 ) and organic (O‐PM2.5 ) soluble extracts] and performed miRNA microarray analysis. A total of 37 miRNAs and 62 miRNAs were altered 1.3‐fold in W‐PM2.5 and O‐PM2.5, respectively. Integrated analyses of miRNA and mRNA expression profiles identified negative correlations between miRNA and mRNA in both W‐PM2.5 and O‐PM2.5 exposure groups. Gene ontology and Kyoto encyclopedia of genes and genomes (KEGG) pathway analyses showed that the 35 W‐PM2.5 target genes are involved in responses to nutrients, positive regulation of biosynthetic processes, positive regulation of nucleobase, nucleoside, and nucleotide, and nucleic acid metabolic processes; while the 69 O‐PM2.5 target genes are involved in DNA replication, cell cycle processes, the M phase, and the cell cycle check point. We suggest that these target genes may play important roles in PM2.5 ‐induced respiratory toxicity by miRNA regulation. These results demonstrate an integrated miRNA‐mRNA approach for identifying molecular events induced by environmental pollutants in an in vitro human model. © 2016 Wiley Periodicals, Inc. Environ Toxicol 32: 302–310, 2017.